A Research on the Incentive Mechanism and Guarantee Measures of High-Quality Running of Shanghai Amateurs Games (Asian Journal of Social Science Studies, 2022)
In 2017, under the background of implementing the national fitness plan and promoting the construction of healthy Shanghai, Shanghai initiated the Amateurs Games system. Also in this year, Li Qiang, secretary of Shanghai Municipal Party Committee, stressed that ‘we should build Shanghai's strategic advantages in development and strive to build four brands of Shanghai service, Shanghai manufacturing, Shanghai shopping and Shanghai culture’. Among them, Shanghai service is in the leading position. As one of the outstanding representatives of Shanghai sports service industry, Shanghai Amateurs Games has become very important to carry out high-quality competitionss to promote brand building. This report based on the analysis of some experts and scholars at home and abroad with an overview of the research on Shanghai Amateurs Games, comb, summarizes relevant literature, expert interview, field investigation, combined with the actual situation of Shanghai city amateur Games, for its high quality run competitions incentive mechanism and safeguard measures to carry out study activities and put forward the optimized route for reference.